Expression of metabolic genes in NK cells is associated with clinical outcomes in patients with severe COVID-19: a brief report - Osuna-Espinoza, Kenia Y.; Mejia-Torres, Manuel G.; Camacho-Ortiz, Adrian; Perez-Alba, Eduardo; Martinez-Castilla, Azalia M.; Salinas-Carmona, Mario C.; Rosas-Taraco, Adrian G. (Frontiers in Cellular and Infection Microbiology, 2025)
Natural killer (NK) cells are innate lymphocytes with cytotoxic activity against tumors and viruses. The pandemic of the coronavirus disease 2019 (COVID-19) has increased the investigation of their role in disease severity. However, their functional status and modulators remain controversial. Recent studies highlighted the role of metabolism in immune function, but metabolic changes in NK cells during SARS-CoV-2 infection remain unexplored. This study compares metabolic (SIRT1, AMPKA, HIF1A, and GLUT1) and inflammatory (NFKB1, NFKB1A, IFNG, and SOCS1) gene expression, and flow cytometry-based assessment of functional markers in NK cells from severe COVID-19 patients (n=15) and the control group (n=10), and their association with clinical outcomes. Severe COVID-19 patients exhibited elevated IFNγ, Granzyme B, and KIR2DL1 expression in NK cells compared to controls (P < 0.005), while LAMP1 was unchanged (P > 0.05). NK cells from deceased patients exhibited significantly lower expression levels of LAMP1 and Granzyme B (P < 0.05). Patients hospitalized >7 days presented lower Granzyme-B+ NK cells (P < 0.05). NK cells from severe COVID-19 patients showed downregulation of HIF1A and GLUT1, and upregulation of NFKB1 (P < 0.05). HIF1A and GLUT1 expression were elevated in patients with >7 days of hospitalization (P < 0.05). SIRT1 expression was higher in patients requiring intubation (P < 0.05). SIRT1, HIF1A, and GLUT1 were upregulated in deceased patients (P < 0.05). In conclusion, we demonstrate that NK cells from patients with severe COVID-19 exhibit increased functional markers and dysregulated metabolic gene expression associated with clinical outcomes.